Lipid and protein deterioration during the chilled storage of minced sea salmon (Pseudopercis semifasciata) - Tironi, Valeria Anahi (2007)
Sea salmon is a very appreciated seafood. The aim of this work was to analyze changes in lipid and protein fractions of minced muscle during chilled storage (1 ± 1 °C). Lipid oxidation was important during the first 6 days of storage according to 2‐thiobarbituric acid (TBA) values determined, decreasing mainly ω3 22:6 fatty acid content. Lipid hydrolysis was evident after 9 days of storage. Interaction compounds between oxidation products and other cellular components were analyzed by fluorescence measurements. The results obtained showed evidence of the formation of interaction products involved, mainly polar components such as proteins. Decreases in myosin and actin thermal stability and myosin denaturation were recorded by differential scanning calorimetry. Solubility of total and myofibrillar proteins decreased after 6 days of storage. The electrophoretic profile of soluble fractions showed an increase in the intensity of bands corresponding to low‐molecular‐weight polypeptides and a decrease in high‐molecular‐weight species. Available lysine content did not change during chilled storage.